Pemanfaatan Limbah Pasir Sandblasting Sebagai Material Perkerasan Kaku - Layang, Samuel; Thathit Suprayogi; Wiratno; Okta Meilawaty; Renna Jessica Sihombing; Frans Putra Ganesa (Universitas Muhammadiyah Surabaya, 2025)
This study aims to determine the compressive strength and flexural strength of concrete using Sandblasting Sand waste and to determine whether concrete using Sandblasting Sand waste can be used as a rigid pavement material. To achieve these objectives, experimental research was carried out in the laboratory using 10 beam specimens. The coarse aggregate used was a combination of Banjarmasin Gravel and Merak Gravel with a proportion of 50% each. There are two variations of the mixture, namely a concrete mixture using Tangkiling Sand and a concrete mixture using Sandblasting Sand. From the test results, it was obtained that the concrete mixture using Tangkiling Sand had an average compressive strength of 22.57 MPa and a flexural strength (fs) of 36.33 kg/cm2. The concrete mixture using Sandblasting Sand has an average compressive strength of 26.55 MPa and flexural strength (fs) of 39.40 kg/cm2. Concrete mixtures with proportions of 50% Banjarmasin Gravel and 50% Merak Gravel, both using Tangkiling Sand and Sandblasting Sand do not meet the requirements for use as rigid pavement because they do not meet the minimum flexural strength of 45 kg/cm2 as required.